Challenges of Financial Management in Companies in the Tourism Sector in AP Vojvodina - Mirović, Vera; Milenković, Nada (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Tourism is one of the sectors most affected by the kovid 19 pandemic. The challenges for companies operating in the field of tourism are certainly greater than those operating in other industries. The aim of this paper is to review the state of the tourism sector in AP Vojvodina in the period before the pandemic, ie. from 2015 to 2019 and during the pandemic, ie. in 2020. The financial analysis of the tourism sector in AP Vojvodina before the pandemic, was performed by the method of descriptive statistical analysis on a sample of 3,456 companies in the sector of tourism. The assessment of the situation in the pandemic year was performed on the basis of available reports of the Statistical Office of the Republic of Serbia for 2020. The results of the research show that in AP Vojvodina, even before the pandemic, there was a downward trend in the company’s net business results. The pandemic has further aggravated the financial position of companies in the field of tourism.